Mutations in KIF27, GNAS and IFT140 genes in a patient with VACTERL association: a case report - Siti Aishah Sulaiman; Nor Azian Abdul Murad; Chow, Yock Ping; Zam Zureena Mohd Rani; Salwati Shuib; Dayang Anita A. Aziz; Hana Azhari; Sharifah Azween Syed Omar; Zarina Abdul Latiff; Rahman Jamal (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
VACTERL association is a rare genetic disorder involving at least three of the following congenital malformations: vertebral defects (V), anal atresia (A), cardiac defects (C), trachea-oesophageal fistula with or without oesophageal atresia (TE), renal anomalies (R) and limb abnormalities (L). Until now, the aetiology of VACTERL association is unknown, particularly at the molecular level. Here, we performed whole exome sequencing (WES) of an infant with VACTERL association. The patient was delivered prematurely at 30 weeks and had 4/6 of the VACTERL malformations. Trio-WES analysis was performed using Torrent Suite and ANNOVAR. Polymorphisms with an allele frequency of >0.01 were excluded, and the remaining variants were filtered based on de novo mutations, autosomal recessive, X-linked and di-genic inheritance traits. In this patient, no homozygous, compound heterozygous or X-linked mutations was associated with VACTERL. However, we identified two heterozygous mutations; KIF27 (ENST00000297814: c.3004A> C:p.N1002H) and GNAS (ENST00000371098: c.205C>A:p.H69N) genes that were inherited from her father and mother respectively. A de novo, IFT140 gene mutation (ENST00000426508: c.683C>G:p.S228C) was also identified in this patient. The VACTERL phenotype in this patient may due to heterozygous mutations affecting KIF27 and GNAS genes, inherited via autosomal recessive trait. In addition, the IFT140 gene mutation may also be involved. These genes are known to be directly or non-directly involved in the sonic hedgehog signalling that is known to be implicated in VACTERL. This is the first report of these genetic mutations in association with VACTERL.